Information technology of 3D object’s rendering - Моргун, К.О. (Science-based technologies, 2017)
The paper considers the information technology of creating three-dimensional objects using computer graphics. Information technology is considered as a coherent process of creating a 3D model, determining the geometry of a 3D model, lighting and preserving an output image. In the paper methods of calculating the point of intersection of the camera ray of the element of the surface of the object when traversing the beam, determining the point of illumination, approaches to optimization of calculations based on the division of the scene, during visualisation, into sections that corresponds of independent flows of calculations. Modelling results presented using known software.